2021
DOI: 10.3390/genes12020283
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Copy-Number Proportions: The Comeback of Sanger Sequencing

Abstract: Determination of the relative copy numbers of mixed molecular species in nucleic acid samples is often the objective of biological experiments, including Single-Nucleotide Polymorphism (SNP), indel and gene copy-number characterization, and quantification of CRISPR-Cas9 base editing, cytosine methylation, and RNA editing. Standard dye-terminator chromatograms are a widely accessible, cost-effective information source from which copy-number proportions can be inferred. However, the rate of incorporation of dye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…However, unlike the female sequence assembly (SRA accession number: ERX2240357), in this case (SRA accession number: SRX7899544), only three haplotypes were found. Moreover, sequence chromatograms of some of the specimens pointed to additional types of females with presumably three banf2 copies, in accordance with the decomposition analysis performed by Tide software (Figures 3b and 4b and Figure S3) [52,53]. We were also able to distinguish male types in Sanger sequencing by an informative SNP within exon 3, which allowed deduction of the gene copy proportion by the peak signal ratio of the C/T nucleotides (Figure 4).…”
Section: The Gene Models Of Banf2 Locus In Oa Hybrid Stocksupporting
confidence: 80%
See 3 more Smart Citations
“…However, unlike the female sequence assembly (SRA accession number: ERX2240357), in this case (SRA accession number: SRX7899544), only three haplotypes were found. Moreover, sequence chromatograms of some of the specimens pointed to additional types of females with presumably three banf2 copies, in accordance with the decomposition analysis performed by Tide software (Figures 3b and 4b and Figure S3) [52,53]. We were also able to distinguish male types in Sanger sequencing by an informative SNP within exon 3, which allowed deduction of the gene copy proportion by the peak signal ratio of the C/T nucleotides (Figure 4).…”
Section: The Gene Models Of Banf2 Locus In Oa Hybrid Stocksupporting
confidence: 80%
“…Indeed, peak-height analyses of Sanger chromatograms of some female individuals from the hybrid Oa stock also supported this model (Figure 4a). For these specimens, banf2w represented approximately 25% of the trace signal according to Tide software [52,53], suggesting a 3:1 ratio for banf2/ban2fw (Figure S3). According to this model, banf2w and banf2c are located on the W chromosome, while banf2a and banf2b are situated on the Z chromosome.…”
Section: The Gene Models Of Banf2 Locus In Oa Hybrid Stockmentioning
confidence: 98%
See 2 more Smart Citations
“…This amplification product, when extracted from agarose gel and sequenced showed that this gene has multiple copies (Figure 2b,c). Investigation of copy-number variation based on Tide analysis for individual fish that had a shift in their sequence (Brinkman et al, 2014;Seroussi, 2021), and peak ratio examination of four SNPs for other individual fish (Fig. S1, Seroussi, 2021) suggested that this gene is in keeping with an octaploid model (Figure 2b,c).…”
mentioning
confidence: 99%